Interactive functional anatomy - Hillman, Susan Kay, 1952-; Primal Pictures Ltd. (London : Primal Pictures Ltd., 2011)
Contains a complete 3-D model of the entire skeleton with muscles, ligaments, bones, arteries, and nerves, complete with detailed text describing each body part and its function.
Title from disc label.
This DVD-ROM is PC and Mac compatible.
System requirements: Operating systems: Microsoft XP, Vista, Window 7, Mac (Intel) OSX 10.4, 10.5, and 10.6 ; Processor speed : 1.5 GHx with 512 MB of RAM ; Disc space: 200 MB ; Screen display: 1024 x 768 screen ; DVD drive.
Keywords: Anatomy